(untitled) (Bangladesh Journal of Zoology, 2021)
The availability and compositions of foods in the aquatic system have a direct influence on nutritional compositions of fish muscle. This research aimed to determine the nutritional compositions of wild and cultured climbing perch, Anabas testudineus, between pre-monsoon and post-monsoon. The proximate compositions, total amino acid, and fatty acid profiles were determined by AOAC, HPLC and GC, respectively. The results in dicated that proximate (e.g., moisture, ash, protein and lipid), amino acid and fatty acid profile varied significantly (p<0.05) between wild and cultured fishes depend on season. The highest amount of moisture (79.62±0.92%) was found in wild A. testudineus and lowest amount of ash (2.50±0.09%) was found in cultured A. testudineus during pre-monsoon. For both cultured and wild A. testudineus, amount of protein was higher in post-monsoon than in pre-monsoon period. The protein and amino acids contents as well as lipid and fatty acids of the fish species showed a significant (p<0.05) seasonal variations. Among the 14 recorded amino acidsthe major amino acids in the total crude protein were histidine, methionine, isoleucine, lysine, glutamic acid, and glycine. The ratio of Essential Amino Acid (EA)/Non-Essential Amino Acid (NEA) was highest (0.34) in cultured fish of post-monsoon season and lowest (0.25) in wild fish of pre-monsoon season. The major fatty acid so wild and cultured A. testudineus were oleic acid (18:1), palmitic acid (16:0), linoleic acid (18:2), stearic acid (18:0), palmitoleic acid (16:1), andmyristic acid (14:0).Some fatty acids [Lauric acid (C12:0), Pentad cyclic acid (C15:0), Arachidic acid (C20:0)]were not detected in cultured fish but present in wild fish. The n-3/n-6 ratio was highest (0.48) in wild fish of post-monsoon season and lowest (0.14) in cultured fish of pre-monsoon season. Therefore, a comprehensive study on wild and cultured climbing perch is required for further confirmation of the result of the present study. Bangladesh J. Zool. 48(2): 365-378, 2020